Die Sammlung. : Kunsthalle zu Kiel. - Beyer-Beckmann, Ute; Kunsthalle zu Kiel (Kiel : Kunsthalle zu Kiel - Christian-Albrechts-Universität - Schleswig-Holsteinischer Kunstverein Kiel, 1999)
Polke, Sigmar ; Nolde, Emil ; Rheinsberg, Raffael ; Jawlensky, Alexej von ; Aktion "Entartete Kunst" ; Aereboe, Albert ; Assig, Martin ; Barlach, Ernst ; Baselitz, Georg ; Baumeister, Willi ; Heckel, Erich ; Hoehme, Gerhard ; Kirchner, Ernst Ludwig ; Nebel, Kai Heinrich ; Richter, Gerhard ; Schmidt-Rottluff, Karl
biografie, bibliografie
Duits
boek